Effects of obesity on outcomes of laparoscopic transabdominal preperitoneal inguinal hernia repair: a retrospective analysis - Dawid Golik; Przemysław Sroczyński; Krzysztof Jędras; Grzegorz Dobkowski; Michał R. Janik (Videosurgery and Other Miniinvasive Techniques)
Introduction: Inguinal hernia repair, particularly the transabdominal preperitoneal (TAPP) technique, is common worldwide. Obesity (body mass index [BMI] ≥30 kg/m2) can influence surgical outcomes, potentially resulting in longer operative time, higher complication rate, and prolonged hospital stay.